Delineation of the Critical Parameters of Salt Catalysts in the N‐Formylation of Amines with CO2. Issue 47 (3rd July 2019) - Hulla, Martin; Ortiz, Daniel; Katsyuba, Sergey; Vasilyev, Dmitry; Dyson, Paul J.
Abstract: N ‐ formylation of amines combining CO2 as a C1 source with a hydrosilane reducing agent is a convenient route for the synthesis of N ‐ formylated compounds. A large number of salts including ionic liquids (ILs) have been shown to efficiently catalyze the reaction and, yet, the key features of the catalyst remain unclear and the best salt catalysts for the reaction remain unknown. Here we demonstrate the detrimental effect of ion pairing on the catalytic activity and illustrate ways in which the strength of the interaction between the ions can be reduced to enhance interactions and, hence, reactivity with the substrates. In contrast to the current hypothesis, we also show that salt catalysts are more active as bases rather than nucleophiles and identify the p K a where the nucleophilic role of the catalyst switches to the more active basic role. The identification of these critical parameters allows the optimum salt catalyst and conditions for an N‐formylation reaction to be predicted. Abstract : Unbound and basic : Almost all salts promote the N ‐ formylation of amines with CO2 . However, not all do it well. Herein, we present the physical parameters of salt catalysts critical for high activity. Namely their basicity, which is linearly proportionate to the catalytic activity of the salt and the extent of ion pairing, which also impacts significantly on the activity.